ANALISIS SIKAP NASIONALISME MAHASISWA PROGRAM STUDI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (PPKn) FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN (FKIP) UNIVERSITAS RIAU - Ayu, Santia Ariska; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study in the background by the rolling of reform era that was inflated by the students brought many changes in all fields in the Unitary State of the Republic of Indonesia. There are positive changes that are certainly beneficial to the community, and also there are negative changes that affect the territorial integrity of the Unitary State of the Republic of Indonesia. The most obvious negative impact is the waning spirit of nationalism and love of the state. The decline of nationalism is also felt among educational circles of Pancasila and Citizenship Education (PPKn) students, therefore the writer wanted to see how the of nationalism attitude of students of Pancasila and Citizenship Education Program (FKIP) of Faculty of Teacher Training and Education (FKIP) University of Riau. The purpose of this study was to find out how of nationalism attitude of students of Pancasila and Citizenship Education Program (PPKn) Faculty of Teacher Training and Education (FKIP) University of Riau. Population in this research is all student of Education Program Pancasila and Citizenship (PPKn) Faculty of Teacher Training and Education (FKIP) University of Riau amounted to 306 people and sample in this research amounted to 76 student. The instruments of data collection are questionnaire, observation, interview and documentation. Data analysis with qualitative descriptive. From the calculation of the percentage of respondents as a whole obtained the answer